Production of Stingless Bees (Trigona sp.) Propolis in Various Bee Hives Design - Agussalim, Agussalim (2015)
ABSTRACT: Trigona sp. is a group of stingless bees that live socially and in colony at the trunk of trees or woods, bamboo hole, sugar palm stalk and in soil hole. Variation in the habitat causes these bees colonies cannot be well-grown and reduce the propolis production. The aim of the research was to determine the production of stingless bees (Trigona sp.) propolis in various bee hives design. This research was started from September to October 2014 in Papak, Genggelang Village District of Gangga, North Lombok Regency West Nusa Tenggara Province. Material of the research was stingless bees (Trigona sp.) as much as 25 colonies taken from sugar palm stalks. Transfer of stingless bees colonies from the stalks to 5 bee hives design (35 x 17.5 x 13.5 cm; 35 x 20 x 15.5 cm; 35 x 20 x 17.5 cm; 37.5 x 20 x 20 cm; 40 x 20 x 20 cm) was performed at night and placed on the nest for about 2 months of the beekeeping process. The research result showed that production of stingless bees (Trigona sp.) propolis in various bee hives design are 20.40 ± 2.07 g; 19.00 ± 2.92 g; 30.80 ± 14.62 g; 21.80 ± 6.30 g and 18.20 ± 7.29 g respectively and did not significantly different (P>0.05). Production of stingless bees (Trigona sp.) propolis is not affected by the bee hives design but affected by the productivity of bee queen, population of workers bee, colony size of bees, activity exit and entrance hives of workers bee. It can be concluded that design 35 x 20 x 17.5 cm resulting higher production of propolis than the other design. Keywords: Stingless bees of Trigona sp., production of propolis, bee hives design